The complete writings of Henry James on art and drama v.2: drama - Henry James (Cambridge University Press, 2016)
"Henry James records in his autobiography a transformative childhood experience in the Louvre when he foresaw the 'fun' that art might bring him. Many of his novels and stories indeed go on to dramatise the circumstances of the artist's life, and their allusions to art are extensive. This complete collection of essays and reviews presents the observations of a major author whose critical judgments have become central to an understanding of late nineteenth-century art. Readers will find James's texts as they first appeared, with a wealth of editorial support, which captures the mood and values of the art scene in Britain, France and America - its interesting minor figures, as well as names still familiar. Many of these items are difficult to access and have not previously been available in a scholarly edition. The editorial apparatus includes a general introduction, a chronology, a textual variants section, and a biographical guide to artists"--